Asperger's Syndrome : a guide for parents and parents and professionals - Attwood, Tony (London : Jessica Kingsley Publishers, 1998)
This is one of the best books for parents and teachers on Asperger Syndrome. The information in this book is also applicable to individuals who are labeled with high functioning autis.
Contest 1. Diagnosis 2. Social Behaviour 3. Language 4. Interests and routine 5. Motor clumsiness 6. Cognition 7. Sensory sensitivity 8. Frequently asked questions
Contiene referencia bibliografica
Keywords: SINDROME DE ASPERGER; ASPERGER'S SYNDROME